Freedom of Opinion After the Constitutional Court Ruled the Fake News Dissemination Crime Unconstitutional - Prahassacitta, Vidya (Journal of Law and Legal Reform, 2024)
Decree of the Constitutional Court No. 78/PUU-XX1/2023 protects freedom of opinion in a public place. That decree rules Article 14 and Article 15 Law No. 1 of 1946 on the Fake News Dissemination Crime unconstitutional. However, does this decree of the Constitutional Court really protect the people’s right to freedom of opinion in a public place? This study is aimed at analyzing freedom of opinion in Indonesia after the decree of the Constitutional Court No. 78/PUU-XX1/2023 was issued. The document study employing a case approach and a law approach shows us that there are still things posing a threat to freedom of expression in a public place. Article 263 and Article 264 Law No. 1 of 2023 on the Penal Code and Article 28 (3) Jo. 45A (3) Law No. 1 of 2024 on the Second Amendment to Law on Electronic Information and Transactions still criminalize a fake news dissemination act. Decree of the Constitutional Court No. 78/PUU-XX1/2023 does not directly rescind the crime in those two laws. Furthermore, the provisions in the content moderation as stipulated in Law on Electronic Information and Transactions may present an obstacle to freedom of opinion in a public place. In the end, we need to request the Constitutional Court to judicially review the other laws on the fake news dissemination crime and to improve the provisions regulating the content moderation.